MICROSCOPY TECHNIQUES ARE EFFECTIVE TOOLS FOR IMPLEMENTING STUDIES IN DAIRY SCIENCE AND TECHNOLOGY (Istituto Lombardo - Accademia di Scienze e Lettere • Incontri di Studio, 2018)
Milk is a complex system where lipids, proteins, sugars and salts are present in different phases, and thus shows a characteristic behaviour during either technological treatments or storage. Lipids are organized as globules, small drops of triglycerides surrounded by a biological membrane that ensures stability of their emulsion. Casein is the main milk protein and is organized as micelles containing salts and strongly hydrated. This last feature has an important effect on the micelle stability. Furthermore, micelle stability is ensured by glycosylated k-casein fragments. Interaction between fat globules and casein micelles are likely to occur since ~1010 globules e 1014 micelles are present in 1 mL of milk and their reactive surface is approximately 0.07 and 4 m2 respectively. Different milk processes, i.e. mechanic or thermal, are responsible for interactions which may vary in number and chemical nature. Microscopy techniques represent an indispensable tool to study milk microstructure during milk processing or even on finished products upon storage. Confocal laser scanning microscopy, through specific probes, is suitable to study phenomena of coalescence among fat globules and fat-protein interactions in fluid milk, gel (clotted milk) or cheese. Transmission electron microscopy and immunogold labelling are used to more deeply investigate either milk components ultrastructure or specific interactions established between the milk fat globule membrane and the casein fractions. Food products are matrices where a multidisciplinary approach is necessary for their study, and microscopy certainly plays a key role.